Hypercontextualized Learning Games: Fantasy, Motivation, and Engagement in Reality. (December 2013) - Islas Sedano, Carolina; Leendertz, Verona; Vinni, Mikko; Sutinen, Erkki; Ellis, Suria
A Hypercontextualized Game (HCG) is a locally designed game that supports its players in gathering context-specific information and in-depth understanding and knowledge regarding the context of a site. LIEKSAMYST, an exciting mobile application, with which visitors can play various games based on stories, was originally developed for the open-air section of the Pielinen Museum and is an example of such a hypercontextualized game. Each individual game (which together make up LIEKSAMYST) was developed in, for and with the co-operation of the Pielinen Museum. In its design, LIEKSAMYST purposefully attempts to connect users to the local history and thus promote affective engagement. With the co-operation of both a local school (Lieksan Keskuskoulu) and the museum authorities, we set out to discover how LIEKSAMYST guides the informal learning experience of Grade 7 pupils. We gathered information from 101 pupils on-site (through questionnaires) and used this data, as well as the pupils' academic grades, to elucidate our study by investigating the relationship between engagement and motivation . The data were analyzed using a quantitative method guided by a qualitative interpretational approach and we found a significant correlation between (a) fantasy and (b) affective and cognitive engagement. The study highlighted the importance of evoking and harnessing both affective and cognitive engagement, through the fundamental element of fantasy, in the game narrative.